Pengaruh Metode Talaqqi dan Metode Muroja’ah Terhadap Peningkatkan Hafalan Al-Qur’an di Sekolah Dasar Islam Terpadu Al-Mufidah Beton Menganti Gresik - Nur Ainiyah; Rohmah Istikomah; Mochamad Nurcholiq; Ashari Ashari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze the influence of talaqqi and muraja’ah methods on improving Qur’an memorization among students at SDIT Al-Mufidah Beton Menganti Gresik, both partially and simultaneously. This research employed a quantitative approach using simple linear regression and multiple linear regression analysis. The population consisted of 115 students, while the sample included 50 students selected through purposive sampling. Data were collected using questionnaires, observation, and documentation. The results indicate that the talaqqi method significantly affects Qur’an memorization improvement with a regression coefficient of 0.388% and a significance value of 0.003%. The muraja’ah method also shows a significant influence with a coefficient of 0.434% and a significance value of 0.000. Simultaneously, both methods significantly influence Qur’an memorization improvement, shown by an F value of 40.513 (Sig. 0.000) and a determination coefficient (R²) of 0.633%. These findings confirm that integrating talaqqi and muraja’ah methods can effectively enhance students’ Qur’an memorization ability.